Enactive Management: Dancing with Uncertainty and Complexity - Garcia-De la Cerda, O (Emerald Group Publishing Ltd., 2014)
Purpose – The purpose of this paper is to present and explain an enactive tool to be used by managers to move effectively in the context of high uncertainty and complexity that organizations nowadays operate. Design/methodology/approach – The approach raises in the enactive management that focusses on the ability of the manager to incorporate distinctions as an observer and self-observer to design interactions that can move the situation to be transformed. The key ontological tool that allow this learning is called CLEHE©. Findings – Using a soft technology as CLEHES, re configures the ways to observe and self-observe of manager and opens the design possibilities of the situation in which the organization is. Managers become choreographers in the sense they can design and move the interactions they observe. The embodied us of this tool requires an educational program that takes the form of hermeneutical laboratory where managers incorporate distinctions in the body and change the perspective they enact. Practical implications – This approach evokes changes in the observer and the enactor situation/ situated in the organizational areas where the manager is responsible. Originality/value – A different and nurturing technology to self-observer and observation, allow enactive management in multiples domains and organizational contexts where the manager dance. The structural dynamics of the CLEHES dimensions creates multiples realities, through enactive conversations in a learning self-awareness process. © Emerald Group Publishing Limited.